Supply , laying , finishing including testing of waterproofing and lightweight concrete in the sunken slab areas for Brac University new campus building at holding no. Kha 224, Merul Badda, Dhaka-1212. - Brac University (Brac University, 2023)
This agreement made between Brac University and M/S Green Concrete to supply, laying , finishing including testing of waterproofing and lightweight concrete in the sunken slab areas for Brac University new campus building project.